Pengabdian Masyarakat dalam Rangka Peningkatkan Gizi dan Kesehatan Ibu dan Anak di Desa Sukorejo Bojonegoro (Lembaga Pengembangan Kinerja Dosen, 2026)
The health of pregnant and breastfeeding women is a crucial determinant of the quality of future generations, particularly during the first 1,000 days of life. However, nutritional problems, such as deficiencies in iron, protein, and essential vitamins, remain prevalent in many regions, especially in rural areas. These conditions may increase the risk of anemia, impaired fetal growth, and reduced maternal and child health outcomes. This community service program aimed to improve the nutritional status as well as the knowledge and awareness of pregnant and breastfeeding women regarding the importance of balanced nutrition in Sukorejo Village, Bojonegoro Regency. The program was implemented through the provision of free balanced nutritious meals tailored to the nutritional needs of pregnant and breastfeeding women, accompanied by health education activities, including counseling sessions and interactive discussions on healthy dietary patterns, food hygiene, and anemia prevention. Program evaluation was conducted through participatory observation and participant feedback. The results indicated an improvement in participants’ understanding of balanced nutrition and positive behavioral changes in daily food selection and consumption. This community service initiative is expected to serve as a sustainable model for improving maternal and child health and preventing nutritional problems at the village level.